Variação do teor de umidade e da densidade básica na madeira de sete espécies de eucalipto Variation of the moisture content and specific gravity in the wood of seven eucalypt species - José Tarcísio da Silva Oliveira (Revista Árvore, 2005)
As variações de umidade e da densidade do lenho das árvores são as principais causas dos defeitos de secagem, como o empenamento e fendilhamento das peças de madeira. Os tipos de madeira presentes em um tronco estão relacionados com as variações dessas duas importantes propriedades físicas. Os gradientes de umidade e da densidade da madeira de sete espécies de eucalipto foram avaliados nas direções radial e longitudinal do tronco de árvores recém-abatidas. Os resultados apontaram uma maior homogeneidade de distribuição de umidade dentro das árvores de E. paniculata e E. citriodora, indicada pelos coeficientes de variação e desvio-padrão. O diferencial de umidade da madeira nas regiões internas do tronco de E. paniculata e E. citriodora foi de 20% e de E. urophylla e E. grandis, de 80%. A densidade básica da madeira aumentou na direção radial do tronco, e cada espécie de eucalipto apresentou um modelo de variação. The occurrence of high moisture and density gradients inside of the tree is related with drying defects, especially those characterized by warp and split of the wood. The unequal behavior of wood pieces due to variation of these two properties can be attributed to differences within the wood that constitutes the log. Considering the importance of knowing the moisture and density gradients in eucalyptus trees, this work had as objective evaluating the variations of the moisture content and specific gravity in the radial and longitudinal directions of the trees of seven eucalypts species. Based on the results concerning the moisture distribution inside the tree, there was a great homogeneity in the species of E. paniculata and E. citriodora, sustained by the low values of variation coefficient and standard deviation. In these species, the moisture differential among the inner and outer parts of the log rarely reached 20%, while for the logs of E. urophylla and E. grandis, this diferencial reached 80%. In spite of the specific gravity general increased in the direction pith-to-bark, each species presented a specific profile of variation, also with variants for each height of the log.